Validation tests for transmission line matrix method in EMC calculations - Özyalçın, M. Orhan; Sevgi, Levent; Topuz, Ercan (IEEE, 2003)
Transmission line matrix (TLM) method algorithm is validated against exact analytical solutions for a typical EMC problem. The two test problems chosen for this purpose are the determination of fields inside a PEC resonator excited by a pulsed source distribution and the determination of the radiated fields from an aperture on the wall of the resonator. Almost perfect agreement was obtained between the TLM solutions and corresponding analytical results both in time and frequency domains. Results show that TLM can be used in an efficient way in addressing SE calculations and can also be applied to the calculation of EM fields in similar complex EM problem environments.
Keywords: Green's Function; Validation; Modeling; TLM Memod